Ano 'yon? ano 'yan? the whats and whys of being Filipino - Baron, Cynthia Sta. Maria; Yulo, Millet Yraola (Quezon City, Philippines Baron Multimedia, 2008)
A dictionary of Filipino slang words and idioms.
Includes index.
College Student
English and Tagalog.